An update of fire needle acupuncture for acute herpes zoster and prevention of postherpetic neuralgia in adults: A protocol for systematic review and meta-analysis. Issue 1 (8th January 2021) - Wang, Jiaxuan; Wang, Xindong; Xia, Hongyan; Zhang, Na; Lin, Shiyu; Zeng, Jingchun; Lin, Guohua
Abstract: Background: Herpes zoster, is one of the most familiar skin diseases in conducted a systematic review and meta-analysis in 2018 showed that fire needle acupuncture can relieve the pain caused by herpes zoster quickly and prevent the outcome of postherpetic neuralgia (PHN), with little side effects. The purpose of this study is to update the systematic review with the latest evidence. Methods: Four English (PubMed, Embase, the Cochrane Library, the Web of Science) and 4 Chinese databases (CNKI, Wanfang, VIP, and CBM) will be searched dating until 30 June 2020 for randomized controlled trials with no language restrictions. In addition, a hand search of the reference lists of included studies will also be done. Adults (aged 18–70) with acute herpes zoster (less than 7 days) using fire needle acupuncture will be included. Pairs of researchers will independently conduct the search, screen titles and abstracts, retrieve full texts of potentially eligible studies, assess the risk of bias, and conduct date extraction and synthesis. If there is any discrepancy in the whole process, consult a third researcher. For meta-analysis, the primary outcome is the pain intensity (visual analogue scale [VAS] pain scale; pain relieve of 30%, duration of pain), and the second outcome is incidence of PHN. A sequential analysis will be done to test the robustness of results of meta-analysis. The quality of evidence will be assessed using GRADE system. Results: The results will be published in a peer-reviewed journal. Conclusion: This study will provide the latest systematic review and meta-analysis of fire needle acupuncture for acute herpes zoster and prevention of PHN.